2015
DOI: 10.1080/19443994.2014.950342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different types of calcium sulfate on the reactivity of cement/Fe(II) system in dechlorination of trichloroethylene

Abstract: A B S T R A C TSeveral studies have been carried out to find out the reactive species in cement/Fe(II) system for the treatment of ground water contaminated with a number of chlorinated organic pollutants such as trichloroethylene (TCE). The previous studies suggest that cement hydration minerals associated with sulfate (SO 2À 4 ) could be one of the reactive species responsible for dechlorination reaction. Calcium sulfate which is a primary source of sulfate in cement has not been studied in detail. Present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The [14]. The dosage of dihydrate form of calcium sulfate and anhydrate (insoluble) form of calcium sulfate was kept at 5% and was added to clinker separately in two glass bottles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The [14]. The dosage of dihydrate form of calcium sulfate and anhydrate (insoluble) form of calcium sulfate was kept at 5% and was added to clinker separately in two glass bottles.…”
Section: Methodsmentioning
confidence: 99%
“…Series of batch experiments were performed to determine the removal of fluoride using four types of cement, cement [14] the highest reactivity in the reduction in pollutant. However, the present study contradicts the findings.…”
Section: Fluoride Removal Efficiency Of Different Types Of Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the presence of calcium sulfate in mixing water has been found to increase the setting time. However, the rate of increase is reduced when a higher concentration of calcium sulfate is present in the mixing water [42]. Moreover, it was reported that mixing water with high pH increases the setting time of paste drastically.…”
Section: Initial Setting Time Of Cement Pastementioning
confidence: 99%
“…The higher the alkalinity, the more accelerated the setting times. This accelerated setting time has been attributed to the formation of gyrolite [42]. The presence of sulphuric acid or hydrochloric acid has been found to decrease the initial and final setting time of paste [43].…”
Section: Initial Setting Time Of Cement Pastementioning
confidence: 99%